Cover Picture: Multivalent Interactions between an Aromatic Helical Foldamer and a DNA G‐Quadruplex in the Solid State (ChemBioChem 20/2016). (27th September 2016) - Mandal, Pradeep K.; Baptiste, Benoît; Langlois d'Estaintot, Béatrice; Kauffmann, Brice; Huc, Ivan
Abstract : The cover picture shows a crystallization droplet containing anti‐parallel hairpin DNA G‐quadruplexes and a racemic mixture of interconverting right‐ and left‐handed helical foldamers. Crystals obtained from this medium reveal a co‐crystal structure of G‐quadruplexes and left‐handed helices only. An actual diffraction pattern from such a crystal is shown in the background. The magnified area indicates multivalent foldamer–DNA interactions in the crystal and shows that the foldamer targets quadruplex loops and grooves and not G‐tetrads. More information can be found in the communication by I. Huc et al. onpage 1911 in Issue 20, 2016 (DOI:10.1002/cbic.201600281 ).